Cost and clinical flow of point‐of‐care urine tenofovir testing for treatment monitoring among people living with HIV initiating ART in South Africa - Melody Wang; Pravikrishnen Moodley; Mlungisi Khanyile; Elliot Bulo; Makhosazane Zondi; Keshani Naidoo; Yukteshwar Sookrajh; Jienchi Dorward; Monica Gandhi; Nigel Garrett; Paul K. Drain; Monisha Sharma (Journal of the International AIDS Society, 2025)
Abstract Introduction Point‐of‐care (POC) urine tenofovir (TFV) tests can provide timely information regarding antiretroviral therapy (ART) adherence to support management of HIV treatment in clinics. However, there are limited data on the costs and feasibility of integrating POC testing into HIV clinics in sub‐Saharan Africa. We characterized clinic flow and implementation costs of POC adherence testing for persons initiating ART in HIV care clinics in South Africa. Methods We conducted a microcosting within a randomized controlled implementation trial of POC TFV test in government clinics in Durban, South Africa (STREAM HIV). Time‐and‐motion observation was conducted between 1st March and 31st December 2022, to assess staff and client time needed for POC TFV testing and counselling. We estimated both financial and economic costs for capital, clinic consumables and personnel using a provider (national government) perspective. Results The estimated cost of POC TFV was USD $13 per client, assuming a clinic volume of 20 individuals initiating ART per month. The largest component costs of POC TFV testing were the test strip consumables, which accounted for 53% of the test cost. The median total time of a clinic visit with a POC TFV test, starting from client registration, was 49:19 (minutes: seconds) (IQR: 29:19–89:35). TFV testing took 9:22 (IQR: 7:35–14:11), taking up 19% of the total clinic visit time, including sample collection, sample loading, TFV test processing and counselling provision based on test results. Overall, 29% of the clinic visit time included direct clinical care and assessment with a provider, with clients spending a median 14:09 (IQR: 10:35–21:22) getting vitals checked, receiving adherence monitoring via POC TFV testing, and collecting their ART refill. Waiting in line for ART took most (48%) of the clinic visit time. Conclusions POC TFV testing can be administered at reasonable costs, requires less than 10 minutes of healthcare provider time, and, therefore, may be feasible to implement in South African clinics. Findings can inform policy and budgetary planning for ART monitoring in South Africa and future cost‐effectiveness analyses of POC TFV testing. Clinical Trial Number NCT04341779